Inactivation of lmo0946 (sif) induces the SOS response and MGEs mobilization and silences the general stress response and virulence program in Listeria monocytogenes - Ładziak, Magdalena; Prochwicz, Emilia; Gut, Karina; Gomza, Patrycja; Jaworska, Karolina; Ścibek, Katarzyna; Młyńska-Witek, Marta; Kadej-Zajączkowska, Katarzyna; Lillebaek, Eva M. S.; Kallipolitis, Birgitte H.; Krawczyk-Balska, Agata (Frontiers in Microbiology, 2024)
Bacteria have evolved numerous regulatory pathways to survive in changing environments. The SOS response is an inducible DNA damage repair system that plays an indispensable role in bacterial adaptation and pathogenesis. Here we report a discovery of the previously uncharacterized protein Lmo0946 as an SOS response interfering factor (Sif) in the human pathogen Listeria monocytogenes. Functional genetic studies demonstrated that sif is indispensable for normal growth of L. monocytogenes in stress-free as well as multi-stress conditions, and sif contributes to susceptibility to β-lactam antibiotics, biofilm formation and virulence. Absence of Sif promoted the SOS response and elevated expression of mobilome genes accompanied by mobilization of the A118 prophage and ICELm-1 mobile genetic elements (MGEs). These changes were found to be associated with decreased expression of general stress response genes from the σB regulon as well as virulence genes, including the PrfA regulon. Together, this study uncovers an unexpected role of a previously uncharacterized factor, Sif, as an inhibitor of the SOS response in L. monocytogenes.